Pengaruh Perbedaan Elevasi Muka Air Tanah Pada Pondasi Telapak Berdasarkan Studi Numerik - Iman, Miftahul; Aminullah, Aminullah (Borneo Engineering : Jurnal Teknik Sipil, 2019)
The south Kalimantan Province has various soil characteristic, the difference of ground water level included . Experimental modeling of foot plate foundations in various ground water level is too difficult to be performed. There were so many variables that need to be evaluated in the modeling. The numerical model was based on finite element method such in Abaqus allowed the modeling of foot plate foundations with the various of ground water level. This study modeled the foot plate foundation structure where located on various ground water level by giving variations of the effect of water level to the elevation of the foundation. Water level variations are determined successively below the foundation elevation, the same as the foundation elevation and above the foundation elevation. The analysis performed is static structure analysis with idealization of 2D shell idealization. The result of the research showed that the ground water level effect the stress and deformation of soil closed to foundation elevation. The stress had been evaluated at the base of the foundation for each ground water level difference correspondently 16,53 MPa, 9.34 MPa and 3.59 MPa. The lowest stresses was occured in ground water elevation above the foundation elevation (78.28%).